Interpretation of the 1/C2 Curvature and Discontinuity in Electrochemical Capacitance Voltage Profiling of Heavily Ga Implanted SiGe Followed by Melt Laser Annealing. (2nd December 2020) - Sermage, B.; Tabata, T.; Ren, J.; Priante, G.; Gao, Y.
Abstract : Electrochemical Capacitance Voltage Profiling (ECVP) is one of the most widely used characterization methods in semiconductor industry to measure the activation of dopants in doped semiconductor materials owing to its low-cost and easy-to-use features. Today, there are some specific industrial needs, for instance reduction of the contact resistance in advanced transistors, for which heavily-doped semiconductor materials must be implemented. A clear challenge addressed to ECVP here is that the interpretation of measured data becomes much more complex in such materials because of the appearance of curvatures and discontinuity on the curve given by the inverse of the square of the capacitance within the space charge zone as a function of the applied polarisation voltage. In this paper, we present a case of silicon-germanium doped by heavy gallium ion-implantation and annealed by melt laser annealing, where a metastable dopant activation can be expected. We develop a fitting model with different deep levels, highlighting their possibly different time constants to provide a more reliable interpretation on the measurements.